PENJAMINAN MUTU BERBASIS CORE VALUES DI MADRASAH ALIYAH PUSAT MENES BANTEN - Arianda Tanjung; Syukur Kholil; Erwan Efendi (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
The aim of this study is to conduct comprehensive disclosure of the Quality Assurance at Madrasah Aliyah Pusat Menes Banten. This researchÂ  is done through a case study on the model of qualitative research.Data were obtainned from observations of researchers through interviews, observation, study of documens and records.The data analysis and and interpretation indicates that; (1) Planning in quality assurance in Madrasah Aliyah based education research, analysis of the facts, the ability of resources, funding sources, define quality standards, determine alternative actions and decision making can be ensured so that the quality of education in Madrasah Aliyah has good quality,(2) Madrasah Aliyah preparation of the work program, arranged on the direction Khithah as a strategic guideline basic philosophy of the movement guide the organization, so as to ensure the quality of education in Madrasah Aliyah, (3) organization working madrasah with apply modern concept, organizational structure, division of task has been set up arranged on work responsibilities, authority and work load, (4) supervision of work through the process control and evaluation when there are errors or deviation will be improved, (5) value basis for the preparation of quality assurance in the from khithah greatly affect the performance of teachers.Â Keywords : penjamin mutu, perencanaan, organisasi, supervisi, core value